Biological Motion Perception Is Affected by Age and Cognitive Style in Children Aged 8–15 - Parisa Ghanouni; Amir Hossein Memari; Monir Shayestehfar; Pouria Moshayedi; Shahriar Gharibzadeh; Vahid Ziaee (Neurology Research International)
The current paper aims to address the question of how biological motion perception in different social contexts is influenced by age or also affected by cognitive styles. We examined developmental changes of biological motion perception among 141 school children aged 8–15 using point-light displays in monadic and dyadic social contexts. Furthermore, the cognitive styles of participants were investigated using empathizing-systemizing questionnaires. Results showed that the age and empathizing ability strongly predicted improvement in action perception in both contexts. However the systemizing ability was an independent predictor of performance only in monadic contexts. Furthermore, accuracy of action perception increased significantly from 46.4% (SD = 16.1) in monadic to 62.5% (SD = 11.5) in dyadic social contexts. This study can help to identify the roles of social context in biological motion perception and shows that children with different cognitive styles may present different biological motion perception.